The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1108/ajems-02-2017-0021
|View full text |Cite
|
Sign up to set email alerts
|

Intellectual capital and competitive advantage in Uganda’s microfinance industry

Abstract: Purpose The paper examines individual contribution of intellectual capital elements to competitive advantage. The purpose of this paper is to explore the weight of individual intellectual capital elements in explaining competitive advantage in Uganda’s microfinance industry. Design/methodology/approach Hierarchical regression was used because of its capacity to indicate precisely what happens to the model as different predictor variables are introduced. Findings This study confirms that the three intellect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
47
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 61 publications
6
47
0
5
Order By: Relevance
“…This is in line with prior studies where Khan, Yang, and Waheed [4] argued that intangible resources such as IC could help firms to utilize their resources efficiently to gain SCP. Moreover, Kamukama and Sulait [22] claimed that IC (such as human capital, structural capital, and relational capital) helps firms in establishing a sustainable competitive position in turbulent markets. In a similar context, our research favors Lee et al [37], who investigated whether IC helps firms to gain tangible and intangible means.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with prior studies where Khan, Yang, and Waheed [4] argued that intangible resources such as IC could help firms to utilize their resources efficiently to gain SCP. Moreover, Kamukama and Sulait [22] claimed that IC (such as human capital, structural capital, and relational capital) helps firms in establishing a sustainable competitive position in turbulent markets. In a similar context, our research favors Lee et al [37], who investigated whether IC helps firms to gain tangible and intangible means.…”
Section: Discussionmentioning
confidence: 99%
“…Especially SMEs, due to a lack of resources and capabilities, can acquire a great advantage of IC, as it is considered less risky and a convenient resource [18]. Top managers are required to intensify initiative to encourage the promotion of IC (human capital, structural capital and relational capital) inside organizations to acquire competitive advantage [22]. In the current era of globalization, IC has been considered as an effective strategy of business firms that leads to financial performance [23] as well as significantly enhances non-financial performance [24], innovative performance [25] and competitive advantage [18].…”
Section: Intellectual Capital and Sustainable Competitive Performancementioning
confidence: 99%
“…Invested resources and the human value-added resources and maintained customer relationships represent competitive advantages has significant effect to performance was used to explain corporate value [14,15]. It is also found that research and development relate to the firms' financial performance [3].…”
Section: The Indirect Effect Explained By the Relation Betweenmentioning
confidence: 99%
“…The main product initially offered by Ugandan MFIs was microcredit, but over time, they have introduced other financial products including savings, insurance, and money transfer. However, as mentioned earlier, many of these MFIs operate at very high costs, which threaten their sustainability (Kamukama, Ahiauzu, & Ntayi, 2010).…”
Section: Mfis and The Need For Youth Tailored Innovationsmentioning
confidence: 99%